ADVANTAGES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE IN E-BUSINESS FOR CONSUMERS - Josimovski, Saso; Pulevska ivanovska, Lidija; Dodevski, Darko (My University, 2023)
In the contemporary e-business environment, the prioritization of great user experiences and exceptional customer service has emerged as a critical objective. This detailed investigation delves deeply into the tactics that provide the foundation for improving user interactions within digital platforms. This is an exploration of the dynamic landscape of digital commerce, highlighting the importance of design principles that prioritize user needs, advanced search capabilities, effortless navigation, and tailored customer assistance. The central focus of the paper is the crucial significance of user interfaces that include both intuitive qualities and a high level of responsiveness across diverse devices. The interfaces play a crucial role in fostering user engagement and cultivating consumer loyalty within the digital domain, serving as a fundamental basis for facilitating favorable interactions between businesses and their clients. E-businesses foster an inclusive and user-centric environment by providing mobile-friendly content and interfaces that accommodate a wide range of user requirements. This approach promotes user exploration, engagement, and retention. The subsequent analysis focuses on the development of site search mechanisms, emphasizing the transition from rudimentary keyword searches to sophisticated search algorithms, the introduction of faceted search options, the integration of visual search capabilities, the implementation of predictive search functions, and the increasing significance of voice search. These innovations operate in conjunction to transform the accessibility of items and services, improve the process of making purchases, and enhance overall user involvement. Users are able to easily find desired items, explore other options, and obtain pertinent information, all of which enhance the overall satisfaction and effectiveness of the e-commerce experience. The investigation ultimately penetrates into the realm of virtual assistants and chatbots, which are driven by artificial intelligence (AI). These digital entities provide both immediate assistance and a range of functionalities designed to improve the overall purchasing experience. Customers have the opportunity to get support, monitor their orders, stay informed about product availability, and participate in virtual trials for apparel or furniture, thanks to the implementation of augmented reality and virtual reality advancements. Fundamentally, these diverse techniques highlight the utmost significance of placing user-centricity, innovation in search and navigation, customization, and AI-driven support mechanisms at the forefront in order to provide seamless, captivating, and effective e-business experiences. In a continuously evolving digital environment, enterprises that use these components are more strategically positioned to fulfill user demands, foster client allegiance, and sustain their competitive advantage.
Keywords: Artificial intelligence, e-business, e-commerce, user experience